Estudio mecánico del asfalto modificado con polímeros y cueros que son utilizados en la elaboración del calzado (2016)
This paper is the result of a cooperation between the Administrative Department of Science, Technology and Innovation (COLCIENCIAS) and Research Group of Pavements and Enginering Materials of the Catholic University of Colombia. The research goal was to understand the physicalmechanical properties of the asphalt cement modified with polymers and leather and also to characterize its chemical properties. The leather used for this modification comes from waste combat boots from the Colombian Army. Several samples were prepared with different combinations of percentages of each of the polymers and leather for the modification of the asphalt cement. The characterization of this material includes stiffness, fluidity and stability in order to find out the percentage with the better performance. After multiple tests, the results show improvements in the mechanical properties of the modified asphalt and leaves the door open for the proper use of polluting material that contributes to reduce the environmental impact.